Pembentukan identitas nasional indonesia: peran bahasa indonesia dalam menumbuhkan rasa kebangsaan dan nasionalisme - hidayah, tadzillah (Maliki Interdisciplinary Journal, 2025)
This journal aims to explore the crucial role of Bahasa Indonesia in shaping our identity as Indonesians, as well as how this language fosters a sense of love for the country and pride in being part of Indonesia among the people. We realize that our country has an abundant wealth of various ethnicities and regional languages. Indonesian, derived from Malay, has long been recognized as a language of communication. It culminated in the Youth Pledge of 1928, where Bahasa Indonesia was officially recognized as the language of unity. This was an important moment that united us, despite coming from diverse backgrounds. It facilitates interaction and understanding between cultures, while instilling the values of unity that unite us all. The use of Bahasa Indonesia in educational institutions, the government, the media, and in everyday conversations strengthens the sense of belonging to the country. In addition, Bahasa Indonesia also serves as a medium to convey the nation's positive values, stories of struggle, and national vision, which in turn encourages a sense of nationalism. However, this research also notes challenges in the global and digital era that can affect the function of Bahasa Indonesia as an identity booster. In conclusion, Indonesian does not only function as a means of communication, but also as an important component in shaping our identity as Indonesians and fostering a sense of pride in it.